2009
DOI: 10.5483/bmbrep.2009.42.1.047
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of Alanine racemase- a spore protein produced by Bacillus anthracis

Abstract: Alanine racemase catalyzes the interconversion of L-alanine and D-alanine and plays a crucial role in spore germination and cell wall biosynthesis. In this study, alanine racemase produced by Bacillus anthracis was expressed and purified as a monomer in Escherichia coli and the importance of lysine 41 in the cofactor binding octapeptide and tyrosine 270 in catalysis was evaluated. The native enzyme exhibited an apparent Km of 3 mM for L-alanine, and a Vmax of 295 μmoles/min/mg, with the optimum activity occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Up to now, it has been shown that many of alanine racemase need PLP as a cofactor [Francois and Kappock, 2007]. However, an alanine racemase from Bacillus anthracis [Kanodia et al, 2008] showed considerable activity without PLP and the activity increased by addition of PLP [Kanodia et al, 2008]. The alanine racemase, in this experiment, is similar to the alanine racemase from B.anthracis in the light of PLP dependency.…”
Section: Resultssupporting
confidence: 51%
“…Up to now, it has been shown that many of alanine racemase need PLP as a cofactor [Francois and Kappock, 2007]. However, an alanine racemase from Bacillus anthracis [Kanodia et al, 2008] showed considerable activity without PLP and the activity increased by addition of PLP [Kanodia et al, 2008]. The alanine racemase, in this experiment, is similar to the alanine racemase from B.anthracis in the light of PLP dependency.…”
Section: Resultssupporting
confidence: 51%
“…The primary amino acid sequence of L. salivarius ALR was analyzed and compared with those of previously reported ALRs (Johnston and Diven 1969 ; Inagaki et al 1986 ; Kanda-Nambu et al 2000 ; Ju et al 2009 ; Kanodia et al 2009 ; Liu et al 2012 ). The amino acid sequences of L. salivarius UCC118, B. pseudofirmus OF4 and G. stearothermophilus IFO 12550 ALRs were retrieved from the UniProt data base ( http://www.uniprot.org/ ), and that of P. putida YZ-26 was obtained from the report by Liu et al ( 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we expressed this L. salivarius ALR gene in Escherichia coli and, interestingly, found that the purified ALR protein was strongly activated in the presence of carboxylates such as acetate and propionate. By contrast, ALRs from Geobacillus and Bacillus species are reportedly inhibited by acetate and propionate (Morollo et al 1999 ; Kanodia et al 2009 ). In addition, ALRs from L. fermentum and Pseudomonas putida are known to be stabilized by acetate, although the mechanism for this effect is not yet known (Johnston and Diven.…”
Section: Introductionmentioning
confidence: 99%
“…Assays were performed to measure alanine racemase on the surface of B. anthracis spores (66,67). Two individual preparations of B. anthracis Sterne spores were diluted to a working stock concentration of 1 ϫ 10 8 CFU/ml.…”
Section: Bacillus Anthracismentioning
confidence: 99%